Proceedings of 2nd Annual Management, Business and Economic Conference (AMBEC 2020) 2021
DOI: 10.2991/aebmr.k.210717.035
|View full text |Cite
|
Sign up to set email alerts
|

Financial Analysis to Predict Financial Distress of Small and Medium-Sized Entities in Malang City

Abstract: The goal of this study is to examine financial ratios to predict financial distress in small and medium-sized enterprises (SMEs) in the city of Malang. The financial ratios used as vector predictors are Liquidity Ratio proxied by Current Ratio (CR), Leverage Ratio proxied by Debt to Asset Ratio (DAR) and Profitability Ratio proxied by Return on Asset (ROA). Based on the results of multiple regression analysis with a significance level of 5%, the results of the study concluded that the model is fit and can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The high ratio of leverage provides the impression to investors that the firms could not efficiently manage their debts, thus increasing the firm's occurrence of financial distress. Similar finding was noted by Susilowati et al (2021) wherein that leverage had a significant influence in predicting financial distress.…”
Section: Leveragesupporting
confidence: 84%
See 3 more Smart Citations
“…The high ratio of leverage provides the impression to investors that the firms could not efficiently manage their debts, thus increasing the firm's occurrence of financial distress. Similar finding was noted by Susilowati et al (2021) wherein that leverage had a significant influence in predicting financial distress.…”
Section: Leveragesupporting
confidence: 84%
“…By nature, financial distress is a condition where a company faces financial difficulties (Kisman et al, 2019) and experiences a lack of cash flow to meet debt obligations (Amoa-Gyarteng, 2021) and a decline in profitability (Susilowati et al (2021) and suffers financial pressure such as poor performance, loss in the income statement for some period (Handoko et al, 2020). According to Mulyaningsih et al (2021), this refers to a situation that is confronted by companies when they suffer financial pressure, such as poor performance, loss in the income statement for some period and they had to struggle to pay their debt.…”
Section: Financial Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a study conducted by [ 43 ] the study suggested financial ratios (liquidity ratio, leverage ratio, and profitability ratio). Profitability has a negative and significant effect; liquidity has no effect.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%